PHPB Attenuated Cognitive Impairment in Type 2 Diabetic KK-Ay Mice by Modulating SIRT1/Insulin Signaling Pathway and Inhibiting Generation of AGEs - Jiang Li; Shaofeng Xu; Ling Wang; Xiaoliang Wang (MDPI AG, 2023)
Diabetes mellitus (DM) has been recognized as an increased risk factor for cognitive impairment, known as diabetic encephalopathy (DE). Hyperglycemia and insulin resistance are the main initiators of DE, which is related to the accumulation of advanced glycation end products (AGEs). Potassium 2-(1-hydroxypentyl)-benzoate (PHPB), a derivative of 3-n-butylphthalide (dl-NBP), has emerged various properties including improved mitochondrial function, antioxidant, anti-neuroinflammation, and neuroprotective effects. The present study aimed to investigate the neuroprotective effect of PHPB against AGEs accumulation in type 2 diabetic KK-Ay mice model with DE and further explore the underlying mechanisms. The results showed that PHPB markedly ameliorated the spatial learning ability of KK-Ay mice in the Morris water maze and decreased AD-like pathologic changes (Tau hyperphosphorylation) in the cortex. Furthermore, we found that PHPB treatment significantly reduced AGEs generation via up-regulation of glyoxalase-1 (GLO1) protein and enhancement of methylglyoxal (MG) trapping, while there was no obvious difference in levels of glucose in plasma or brain, contents of total cholesterol (TC), triglycerides (TG), and plasma insulin. Also, PHPB treatment improved the insulin signaling pathway by increasing sirtuin1 (SIRT1) deacetylase activity and attenuated oxidative stress evidenced by elevating glucose-6-phosphate dehydrogenase (G-6-PD) protein expression, promoting the production of reduced glutathione (GSH) and reduced nicotinamide adenine dinucleotide phosphate (NADPH), restoring mitochondrial membrane potential, increasing adenosine triphosphate (ATP) generation, and reducing malondialdehyde (MDA) levels in the brain. Taken together, PHPB exhibited a beneficial effect on DE, which involved modulating the SIRT1/insulin signaling pathway and reducing oxidative stress by inhibiting the generation of AGEs.